Midterm Outcomes Talocalcaneal Coalition Arthroscopic Resection in Adults - Qinwei Guo MD (Foot & Ankle Orthopaedics, 2023)
Category: Arthroscopy; Hindfoot Introduction/Purpose: Arthroscopic resection3-term outcomes. However, the midterm outcomes of this approach remain uncertain. Methods: We performed a retrospective study of patients who underwent arthroscopic resection for symptomatic TCC. The patients were divided into 2 groups (group P, patients with isolated posterior facet coalition; and group MP, patients with both middle and posterior facet coalition). The preoperative and postoperative visual analog scale (VAS) scores for pain and American Orthopaedic Foot & Ankle Society (AOFAS) scale scores were calculated. The postoperative AOFAS and VAS scores between the 2 groups were analyzed. Patient satisfaction was also assessed. Results: Thirty-two patients were included in this study. The mean age at the time of surgery was 26.0 8.5 years, and the mean follow-up period was 56.9 18.0 months. Postoperative VAS and AOFAS scores improved more significantly than preoperative scores. At the final follow-up, excellent and good subjective outcomes were attained in 26 patients (81%), fair and poor outcomes in 6 patients (19%). There were no statistical differences in the postoperative AOFAS (91.0 7.0 vs 85.8 10.8, P = .532) and VAS score (2.1 1.7 vs 4.0 2.6, P = .537) between patients with the ratio of coalition/posterior facet more than or less than 50%. Conclusion: We found that TCC arthroscopic resection was generally associated with reasonable outcomes at midterm follow-up.